Nutritional Diversity and Antioxidant Activity of Two Indigenous Quince Ecotypes from Rawalakot, Azad Jammu and Kashmir - Noosheen Zahid; Mehdi Maqbool; Majid Mahmood Tahir; Abdul Hamid; Aqeel Ahmad; Muhammad Shafique Khalid; Haseeb ur Rehman; Nasir Masood; Shahid Iqbal Awan; Javaid Riffat Khan; Asgar Ali; Syed Zulfiqar Ali Shah (Journal of Food Quality)
Quince fruit is mostly used to produce functional products. Recently, the value of this crop has increased due to demand as industrial raw material. The state of Azad Jammu and Kashmir and specifically Rawalakot, District Poonch, is blessed with climatic conditions which are very much suitable for quince production, and therefore, a huge plantation could be found in wild. In this regard, this study was designed to collect two different accessions of quince (apple-shaped quince (ASQ) and pear-shaped quince (PSQ)) from three different locations (Dhamni (elevation: 5431 ft), Shamsabad (elevation: 5374 ft), and Drake (elevation: 3378 ft)) of Rawalakot, District Poonch, and analyze their physicochemical and mineral nutrients of fruit and the soil. Correlation coefficients were established pairwise. Results showed that physicochemical nutrients were significantly (P≤0.05) higher in ASQ fruits as compared with PSQ fruits. Further, fruits collected from location at higher elevation (Dhamni) showed better results as compared with fruits collected from lower elevations. Moreover, increased amount of nitrogen contents in the soil resulted in increased fruit weight. Similarly, fruit quality indices and bioactive compounds showed a positive correlation with the increased soil nutrient contents. These prediction models for quality of quince could be useful in guiding plant nutrition status and for enhancing fruit production in this region.